(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Importance of visual art in improving the effectiveness of other subjects in general secondary schools. Also, information about the goals and tasks of visual art education in general secondary schools, the content of classes. information is provided.